PERILAKU DAN MAKNA VERBA DALAM BAHASA MADURA - Akhmad Sofyan (Humaniora, 2012)
This study is aiming at studying the category and the meaning of verb in Madura language. The problem to study is how to know: firm or morphological category, syntactic category, and meaning of verbs in Madura language in enjd'-iyd. Research method applied in this study is descriptive-qualitative method. The data of this study is synchronic which is gained by having interview through open questionnaire. Though stem and base are singular, stem can only stand alone when it is imperative. Transitive can be mono-transitive, transitive, and transitive intransitive. Passive construction can be categorized as anti-active, and imperative can be categorized as anti-passive. Based on the meaning of verb in Madura language consists of causative verb, reciprocal verb, reflexive verb, locative verb, repetitive verb, and imperative verb.